Porosity Identification of Carbonate Core Reservoir Using Digital Rock Physics Method - Sidiq, Irsyad Nuruzzaman; Niyartama, Thaqibul Fikri (Proceeding International Conference on Science and Engineering, 2017)
Indonesia is an archipelago country so rich with coral reefs that are a major component of the carbonate rock constituents. Where as much as 40% of carbonate rocks in Indonesia is a hydrocarbon reservoir is still rarely done exploration. This is because conventional hydrocarbon exploration technology has not been able to provide detailed information about the physical quantities. Hydrocarbon exploration technologies currently leads on digital technology to know the physical quantities of a reservoir of more detail such as porosity. Porosity which is physical quantities related to the presence of hydrocarbons in the pores of rocks. Digital Rock Physics (DRP) is a digital image-based method as an alternative method to find the physical quantities of rock samples to make it more effective and efficient. This study aims to identify the physical quantity using the method of porosity of the DRP until obtaining porosity of rock core carbonate reservoir by analyzing the binary image of the two rock cores from the same reservoir but has different dimensions to find out the exact core rocks to analyze the value of porosity. Binary image obtained from a scanned image of a projection of rock that has been reconstructed to become the greyscale image and have gone through the process of thresholding. The results of this study showed that the method can identify the physical quantities of DRP porosity and non-damaging rock pore structure (non-destructive). Analysis of the porosity of the rock core with histogram variations performed (by adjustingting the histogram), using the otsu method of thresholding and pixel size of the image has high (5.343750 ?m) used to analyze the value of porosity. The porosity values acquired for 18.040 and has precision 96.20%.